Research progress of implantable materials in antibacterial treatment of bone infection - Xiang, Binqing; Jiang, Jingui; Wang, Heng; Song, Lei (Frontiers in Bioengineering and Biotechnology, 2025)
Bone infection is an infectious disease characterized by the accumulation of various pathogens in bone tissue, often causing significant suffering to patients. Current therapeutic approaches for bone infections predominantly rely on the postoperative application of implantable antibacterial materials, highlighting their essential role in clinical treatment. In this review, we systematically analyze research progress in antibacterial implant materials for Bone infection from 2019 to 2025. Materials are classified into four categories based on matrix composition: metal-based composite implants, bioceramic-based composite implants, polymer-based composite implants, and other composite implant materials, with dedicated focus on the limitations of each material type. The deterioration effects of these materials are also thoroughly analyzed. Finally, we present our own insights regarding future development directions of antibacterial implant materials. This review aims to provide practical references and research perspectives for advancing antibacterial implant material development.